Exergy Analysis of Frost-free Air-source Heat Pump System - Zhang Yuhang; Qiu Junjun; Zhang Xiaosong; Xie Lingyun (Zhileng xuebao, 2020)
This study proposes a "one tower with three functions" solution for a dehumidification type frost-free air-source heat pump (ASHP) system, which can not only solve the frost problem of traditional ASHP systems in winter, but also improve the performance of the units in summer. The effects of air temperature, humidity, mass flow rate, solution temperature, and mass concentration were studied under dehumidification conditions. Additionally, solution mass concentration, the effect of solution temperature under regenerative conditions on the air exergy of the inlet and outlet, dehumidification/regenerative exergy, system input, output exergy, and exergy efficiency were studied by constructing the test bench. The results show that under dehumidification, there is an increase in the dehumidification exergy with an increase in the air temperature, air mass flow rate, and solution mass flow rate, and a decrease in the air humidity, solution temperature, and solution mass concentration. Additionally, there is an increase in the system exergy efficiency with an increase in the air temperature, humidity, air mass flow rate, mass flow rate and mass concentration of the solution, and a decrease in the solution temperature, air humidity and mass concentration of the solution. These have an insignificant effect on the exergy efficiency when the efficiency is up to 0.201. Under regenerative conditions, there is an increase in the regeneration exergy with an increase in the solution mass concentration and solution temperature. There is also an increase in the system exergy efficiency with an increase in the solution mass concentration, and a decrease in the solution temperature. The solution temperature has an insignificant effect on the exergy efficiency, when the efficiency is up to 0.1088. The efficiency of this system is higher than that of a conventional ASHP system under experimental conditions.